Transition and justice : negotiating the terms of new beginnings in Africa - Anders, Gerhard; Zenker, Olaf (Hoboken, N.J. : Wiley-Blackwell, 2014)
"This book examines a series of cases where peaceful 'new beginnings' have been declared after periods of violence and where transitional justice institutions played a role in defining justice and the new socio-political order"--
Machine generated contents note: Notes on Contributors 1 Transition and Justice: An Introduction Gerhard Anders and Olaf Zenker 2 Making Good Citizens from Bad Life in Post-Genocide Rwanda Simon Turner 3 Performing Repatriation? The Role of Refugee Aid in Shaping New Beginnings in Mauritania Marion Fresia 4 Conflicting Logics of Exceptionality: New Beginnings and the Problem of Police Violence in Post-Apartheid South Africa Steffen Jensen 5 The 2011 Toilet Wars in South Africa: Justice and Transition between the Exceptional and the Everyday after Apartheid Steven Robins 6 New Law against an Old State: Land Restitution as a Transition to Justice in Post-Apartheid South Africa? Olaf Zenker 7 Transitional Justice, States of Emergency and Business as Usual in Sierra Leone Gerhard Anders 8 'When we Walk Out, What was it all About?': Views on New Beginnings from within the International Criminal Tribunal for Rwanda Nigel Eltringham 9 New Start or False Start? The ICC and Electoral Violence in Kenya Sabine Hohn 10 Justice without Peace? International Justice and Conflict Resolution in Northern Uganda Kimberley Armstrong 11 The Violence of Peace: Ethnojustice in Northern Uganda Adam Branch Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Peace-building -- Africa -- Case studies; Transitional justice -- Africa -- Case studies; Truth commissions -- Africa -- Case studies; POLITICAL SCIENCE -- Economic Conditions; Peace-building.; Transitional justice; Truth commissions; Africa; Electronic books; Case studies